Inklusiwiteit as evangelie - Eck, Ernest Van (HTS teologiese studies, 2009)
In antiquity group identity was based upon cultural ethnicity. Groups used their ethnicity to define and delineate themselves as unique Ethnicity was determined by characteristics like family (kinship), name, language, homeland, myths of common ancestry, customs, shared historical memories, phenotypical features and religion. The Jewish temple religion and law-abiding Jews in the early church (as depicted in Acts and the congregations of Paul) also used their ethnic identity as argument for justifying exclusion of other groups/ethnic peoples from respectively the Temple and the early church. Jesus, Acts and Paul, on the contrary, proclaimed that ethnicity meant nothing when it comes to being in God’s presence, being part of the early Christ-followers, or being part of any local (Pauline) congregation. For this reason, it can be concluded that the New Testament bears witness to an inclusive ecclesiology.